Faktor Penyebab Tidak Tersedianya Berkas Rekam Medis Di Bagian Filling Pada Saat Pelayanan Di Rumkital Dr. Ramelan Surabaya - Ani Nuraini; Gamasiano Alfiansyah; Indah Muflihatin (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2021)
Based on a preliminary study at RUMKITAL Dr. Ramelan Surabaya in March 2020, there was a problemwith the unavailability of medical record files in the filling due to files not returned from poly, and there weremisfiles. It caused longer file provisioning time and delayed service in poly because the officer needs timeto search files that did not exist in storage. The purpose of this study was to determine the factors causingthe unavailability of medical record files in storage. The type of research used a qualitative method. Datacollection techniques used interviews and observation. The results obtained; the factors that causeunavailability of medical record files in the filling seen from 5M factor were as follows. Based on man factor,there is education and officer work experience. The money factor, there is no special fund for providing lostfile folders. The method factor, there is medical record missfile. The material factor, there are broken filefolders so that the contents of these folders could be separated from the file folders. The machine factor,tracer utilization is not optimal. So, the suggestion is to add the color code on the numbering section ofmedical record folder so that it will be easier to store and align medical record documents